HUKUM WARIS ISLAM DARI SUDUT PANDANG HUKUM BERKEADILAN GENDER - Bahriayub Bahriayub (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2020)
AbstractThis study aims to determine the difference heirs of men and women in Islam, different parts of the heirs of men and women in the concept of two to one in Islam and the differences between the heirs of men and women according to gender analysis. Data analysis methods used by the author in this thesis is a qualitative descriptive method which provides an overview of the logical flow of data analysis as well as providing input on qualitative data analysis techniques were used. Once that is done on analyzing the comparison between diverse data and then analyze each other, so that can know the elements that are relevant and irrelevant between Islamic inheritance law with the concept of gender, in order to draw a conclusion.The results of the research in this study; section of a boy with two girls section 2:1. 2:1 that is loaded with the values of justice, arguing that men have obligations from material things exceeds that of women. The concept of gender-equitable distribution of inheritance between men and women equal 1:1, because the provision of a fair is not 2:1.